PENGEMBANGAN MEDIA PEMBELAJARAN KARTU PECAHAN BERBASIS QR CODE PADA SISWA KELAS V DI SD NEGERI - Patamani, Tri Yulianti; Husain, Rusmin; Marshanawiah, Andi; Pulukandang, Wiwy Triyanty; Aries, Nur Sakinah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The purpose of this study was to develop a fraction card learning media based on QR Code that meets the criteria of practicality and effectiveness in learning mathematics on fraction material, especially on fractions with the same denominator in class V SDN No.66 Kota Timur, Gorontalo City. This study is a development research using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility of the fraction card media based on QR Code was tested by a team of experts. The validation results showed that this media obtained an average percentage of 92.27% which was categorized as very feasible for use by teachers and students in elementary schools. To test the practicality, the researcher used a teacher observation sheet, which showed a total score of 38 out of a maximum score of 40, with an average practicality reaching 95%, falling into the very practical category and the student instrument sheet showed a total average score of 37.5% falling into the practical category. In terms of effectiveness, the application of media in class V SDN No.66 Kota Timur, Gorontalo City was measured through pretest and posttest. As a result, the average pretest score of 43.2 increased to 84 in the posttest, with a difference in increase of 40.8 %. The level of effectiveness of the QR Code-based fractional card media based on calculations reached 72%, indicating that the QR Code-based fractional card media is included in the effective category. Based on these results, the QR Code-based fractional card media has proven to be effective and feasible to use in learning in elementary schools. ABSTRAKTujuan penelitian ini adalah mengembangkan media pembelajaran kartu pecahan berbasis QR Code yang memenuhi kriteria kelayakan kepraktisan, dan efektifitas dalam pembelajaran matematika pada materi pecahan khususnya pada pecahan berpenyebut sama di kelas V SDN No.66 Kota Timur Kota Gorontalo. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model pengembangan ADDIE, yang mencakup tahap analysis, design, development, Implementation, dan Evaluation. Kelayakan media kartu pecahan berbasi QR Code diuji oleh tim ahli. Hasil Validasi menunjukkan bahwa media ini memperoleh rata-rata presentase sebesar 92,27 % yang dikategorikan sebagai sangat layak digunakan oleh guru dan siswa di SD. Untuk menguji kepraktisan, peneliti menggunakan lembar observasi guru, yang menunjukkan total skor 38 dari skor maksimal 40, dengan rata-rata kepraktisan mencapai 95%, masuk dalam kategori sangat praktis dan lembar instrument siswa menujukkan total skor rata-rata 92.8 % masuk dalam kategori sangat paraktis. Dalam aspek efektivitas, penerapan media di kelas V SDN No.66 Kota Timur Kota Gorontalo diukur melalui pretest dan posttest. Hasilnya, rata-rata nilai pretest sebesar 43,2 meningkat menjadi 84 pada posttest, dengan selisih peningkatan sebesar 40,8 %. Tingkat efektivitas media kartu pecahan berbasis QR Code berdasarkan perhitungan mencapai 72 %, menunjukkan bahwa media kartu pecahan berbasis QR Code termasuk dalam kategori efektif. Berdasarkan hasil ini, media kartu pecahan berbasis QR Code terbukti efektif dan layak digunakan dalam pembelajaran di SD.